Meaning and Ethical Implications of QS. At-Ṭalaq 2–3 as the Verse of One Thousand Dinars in Hasbi Ash-Shiddieqy’s Tafsir An-Nuur - Khairul Udin; Hasan Bakti Nasution (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study examines Muhammad Hasbi Ash-Shiddieqy’s interpretation of QS. At-Ṭalāq: 2–3, widely known as the “verse of one thousand dinars,” through a text-based exegetical analysis. The study focuses on Hasbi’s contextual-rational approach in interpreting the verse, especially the relationship between spiritual values such as taqwa and tawakkal and ethical responsibility within Qur’anic legal discourse. Using a qualitative method based on library research and content analysis, the study shows that Hasbi explains the normative-legal setting of divorce and waiting periods while developing an ethical framework in which divine provision (rizq) is linked to moral discipline and lawful conduct. The findings indicate that, in Hasbi’s interpretation, QS. At-Ṭalāq: 2–3 functions as a normative structure that integrates legal obedience, spiritual assurance, and ethical accountability. Sustenance is understood in material and moral terms, including ease of affairs, inner tranquility, and socially responsible behaviour grounded in taqwa. Hasbi frames the verse as a moral orientation that guides personal integrity and social conduct in contexts shaped by Qur’anic law. This study contributes to Qur’anic exegetical scholarship by presenting a socio-ethical reading of QS. At-Ṭalāq: 2–3 based on the internal reasoning of Hasbi Ash-Shiddieqy’s Tafsīr al-Qur’anul Majid (An-Nuur). Through a systematic mapping of the relationship between taqwa, tawakkal, rizq, and ethical responsibility, the study highlights how text-based contextual exegesis can connect legal, spiritual, and ethical dimensions within Indonesian Qur’anic interpretation.